Progress on scaling up integrated services for sexual and reproductive health and HIV - Clare Dickinson; Kathy Attawell; Nel Druce
This paper considers new developments to strengthen sexual and reproductive health and HIV linkages and discusses factors that continue to impede progress. It is based on a previous review undertaken for the United Kingdom Department for International Development in 2006 that examined the constraints and opportunities to scaling up these linkages. We argue that, despite growing evidence that linking sexual and reproductive health and HIV is feasible and beneficial, few countries have achieved significant scale-up of integrated service provision. A lack of common understanding of terminology and clear technical operational guidance, and separate policy, institutional and financing processes continue to represent significant constraints. We draw on experience with tuberculosis and HIV integration to highlight some lessons. The paper concludes that there is little evidence to determine whether funding for health systems is strengthening linkages and we make several recommendations to maximize opportunities represented by recent developments.